Media framing on covid-19 booster shots news reporting in Malaysia : a content analysis of the star online - Lim, Lai Hoon (Penerbit Universiti Kebangsaan Malaysia, 2022)
As of May 2022, the death toll of the Covid-19 pandemic in Malaysia reached more than 35,000. To battle the pandemic, since February 2021, Malaysia accelerated its vaccination program nationwide and has become one of the countries with the highest vaccination rate. However, the new Omicron variant set the alarm to the country again for a new wave is approaching. People in the country who have completed two doses of the Covid-19 vaccine were urged for the booster shot. As most people get to know public health and policy information from mediated sources, news media play a crucial role in communicating the importance and the urgency of booster shots. This study examined the salient news themes and the media framing on booster shot news reporting in the highest circulated newspaper in Malaysia, The Star Online. The news about booster shots were content analysed from 1 August to 31 December 2021 where the extensive stories were covered within these 5 months. This study aimed to advance knowledge on Covid-19 booster shot news coverage from a framing perspective. Based on the principle that media have a momentous effect, frames enable audiences to discover a particular point of view in a given situation that was set more noticeably. It takes an inductive approach to the analysis. The findings revealed vaccine information is the dominant news theme where the framing generally carried an urging tone. It concluded media framing of the Covid-19 booster shot transformed the infodemic into informing, assuring, and urging modes in confronting the new wave of a health crisis.